The Hidden Curriculum and Classroom Procedure: Informed Personal Views of Teachers - Boadu, Kankam; Boadu, Gideon; Nyame, Gloria (Advances in Social Sciences Research Journal, 2020)
The study examined how teachers perceived the hidden curriculum. A sample size of twenty teachers was purposively selected and involved in the study. Data were collected through interviews, and the emerging themes formed the focus of the analyses. The study found that teachers possessed a good understanding of the hidden curriculum and its features. Again, teachers perceived the hidden curriculum as important to the teaching and learning process. It was also observed that due attention should be given to its uses. It was concluded that teachers perceived the hidden curriculum positively as it matters to effective teaching and learning.